Relationship Between Mathematics Self-Efficacy and Problem-Solving Ability through the Jigsaw Cooperative Learning Model - Jufri Jufri; Detri Amelia Chandra; Syed Asif Ali (International Journal of Mathematics and Science Education, 2024)
This study investigates the relationship between mathematics self-efficacy and problem-solving ability, exploring the role of the Jigsaw cooperative learning model in enhancing both factors. Self-efficacy, defined as students' belief in their ability to successfully perform mathematical tasks, has been shown to significantly impact students' problem-solving capabilities. The research focuses on understanding how this belief influences academic performance and how the Jigsaw model, which fosters collaborative learning, affects students’ self-efficacy and problem-solving skills. A survey-based research design was employed, with participants consisting of university students enrolled in mathematics courses. Data collection involved administering a self-efficacy scale to assess students' confidence in solving mathematical problems and a problem-solving test to evaluate their abilities. Path analysis was used to determine the relationship between self-efficacy and problem-solving skills, and the effect of the Jigsaw model was evaluated by comparing pre- and post-test scores between the experimental and control groups. The results revealed a strong positive relationship between self-efficacy and problem-solving ability (β = 0.45). Additionally, the Jigsaw model significantly enhanced this relationship, improving both students' self-efficacy and problem-solving performance. These findings highlight the importance of fostering self-efficacy in mathematics education and the effectiveness of the Jigsaw cooperative learning model in achieving this goal. The study provides valuable insights into improving teaching strategies in mathematics, particularly for subjects requiring critical thinking and problem-solving skills, by promoting a more interactive and supportive learning environment.